ChemInform Abstract: Strongylophorines, New Protein Tyrosine Phosphatase 1B Inhibitors, from the Marine Sponge Strongylophora strongilata Collected at Iriomote Island. Issue 1 (17th December 2015) - Lee, Jong‐Soo; Abdjul, Delfly B.; Yamazaki, Hiroyuki; Takahashi, Ohgi; Kirikoshi, Ryota; Ukai, Kazuyo; Namikoshi, Michio
Abstract: The new meroditerpene 26‐O‐ethylstrongylophorine‐14 (I) is isolated from the Okinawan marine sponge Strongylophora strongilata together with six known strongylophorines.